Evaluation of heat stress in 4- and 6-row freestall buildings located in northwest Iowa - John F. Smith; Joseph P. Harner; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2001)
A trial was conducted in the summer of 2000 to evaluate the effect of 4- and 6-row freestall barns located in northwest Iowa on barn temperature, barn humidity, and respiration rates of lactating Holstein cows. Temperature, temperature-humidity index (THI), and respiration rates were greater in 6-row than 4-row freestall barns. Respiration rates were greater in 6-row versus 4-row buildings. The magnitude of difference in the temperature and THI variables may not explain the differences detected in respiration rates. It is possible that a relationship between animal density and social interaction could increase respiration rates when animal density is increased. It may also be possible that the level of mechanical ventilation required to keep cows comfortable in 6- row barns may be greater.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Heat stress; Freestalls; Cow comfort